Experimental investigation of locally available Torai (luffa cylindrica) as evaporative cooling pads. Issue 1 (31st December 2023) - Mishra, Prabhat Ranjan; Somwanshi, Aneesh; Gaba, Vivek Kumar
ABSTRACT: This work presents an experimental evaluation of the performance of a cooling pad made from the locally available material "Torai" (luffa cylindrica). Different performance parameters that define the cooling performance of the proposed pad, such as the exit air temperature, degree of cooling, saturation effectiveness, cooling potential, and coefficient of performance, have been experimentally investigated. Results show that the overall cooling performance (cooling potential, degree of cooling, effectiveness, and coefficient of performance) increases by increasing the pad thickness. For a given pad an increase in air velocity decreases the saturation efficiency and degree of cooling. The maximum saturation effectiveness and coefficient of performance found for a 7 cm pad at 1.5 m/s air velocity are 65.9% and 8.53, respectively. The rate of water evaporation increases by increasing the pad thickness and air velocity. The maximum water evaporation rate found is 1.4 g/s for a 7 cm pad at 1.5 m/s air velocity. The water retention capacity of the proposed pad material is about 78 g. Moreover, it may be concluded that the proposed pad shows reasonably good performance to be employed as a pad material for direct evaporative coolers. The cost of manufacturing a pad 30.48 cm 2 is between Rs130 (US$1.625) and Rs234 (US$2.925).